Mentalizing in the development and treatment of attachment trauma - Allen, Jon G., ....- (London : Karnac, 2013)
This book brings together the latest knowledge from attachment research and neuroscience to provide a new approach to treating trauma for therapists from different professional disciplines and diverse theoretical backgrounds. The field of trauma suffers from fragmentation as brands of therapy proliferate in relation to a multiplicity of psychiatric disorders. This fragmentation calls for a fresh clinical approach to treating trauma. Pinpointing at once the problem and potential solution, the author places the experience of being psychologically alone in unbearable emotional states at the heart of trauma in attachment relationships. This trauma results from a failure of mentalizing, that is, empathic attunement to emotional distress. Psychotherapy offers an opportunity for healing by restoring mentalizing, that is, fostering psychological attunement in the context of secure attachment relationships—in the psychotherapy relationship and in other attachment relationships. The book gives a unique overview of common attachment patterns in childhood and adulthood, setting the stage for understanding attachment trauma, which is most conspicuous in maltreatment but also more subtly evident in early and repeated failures of attunement in attachment relationships. For the first time, the burgeoning literature on mindfulness is integrated with the overlapping literature on mentalizing. Current research in neuroscience is linked to the main clinical concerns: attachment, mentalizing, mindfulness, and trauma. Creatively integrating these diverse perspectives, the author offers an up-to-date scientific explanation of trauma and treatment while writing in plain language without jargon for a broad audience. Thus the book is not only an essential resource for psychotherapists and counselors but also an ideal guide to give to clients to help them understand their condition and the process of healing.
Includes bibliographical references (p. 289-325) and index.
Keywords: Affective neuroscience; Attachment behavior; Attachment disorder -- Treatment; Empathy; Gehechtheidsrelatie; Loneliness; Mentalisatie; Psychic trauma -- Treatment; Psychotherapie